- #1

Plutonium88

- 174

- 0

**Solve the Equation... getting rid of square roots PLZ**

1+ √((1+x)√(x^2-24)) = x

(x*√(x^2-24)) = (x-1)^2 (Square both side)

(-1)+1+(x^√(x^2-24) = (x^2 - 2x +1)-1

x^2(x^2-24) = (x^2 -2x)^2 (Square both sides)

x^4 -24x^2 = (x^2 - 2x)^2

x^4 -24x = x^4 - 4x^3 +4x^2

0 = -4x^3 +4x^2 +4x^2

0 = 4x^2 +4x+ 24

4x^2 -4x -24 = 0

What mistake am I making...

I honestly have tried a bunch of different times, and i had another student check it for me, and i can't catch the mistake I'm making!